Detecção dos genes de virulência e identificação do perfil clonal de isolados de Staphylococcus aureus colonizantes de nasofaringe otbtidos em estudo de base populacional - Abraão, Lígia Maria [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Recent findings show an increase on the incidence and severity of Staphylococcus aureus infection. This fact is worsened by the wide dissemination of the methicillin-resistant S. aureus (MRSA) isolates in hospitals and its recent introduction in the community settings. The nasal colonization in asymptomatic individuals remains the main factor responsible for the persistence and dissemination of S. aureus in the human population. Thereby, nasal carriage surveys are an important tool in order to estimate the total S. aureus burden and the MRSA in the community. Besides, understanding the bacterial-host relationship and the virulence factors involved is necessary in order to manage the infections that jeopardize the population’s health. The present study aims at investigating the clonal distribution of S. aureus and MRSA strains in an urban population area in Botucatu, SP, identifying both the prevalence of the virulence determinants together to the associated risk factors in samples obtained from the nasopharynx of healthy individuals from Botucatu. A total of 223 S. aureus samples isolated from nasal secretions were submitted to the antimicrobial susceptibility tests through the disk-difusion method with oxacillin and cefoxitin disks. The E-test method with oxacillin was applied in order to obtain the Minimum Inhibitory Concentration (MIC) among oxacillin disk resistant samples. Afterwards, PCR (Polimerase Chain Reaction) was carried out for the detection of the mecA gene and of the following virulence genes: enterotoxins (sea, seb and sec), toxic shock syndrome toxin (tst), exfoliative toxin A and B (eta, etb), Panton-Valentine Leukocidin (lukS-PV and lukF-PV), alphaand delta-hemolysins (hla and hld), and biofilms (icaA and icaD). The PFGE molecular typing was employed in order to determine the prevalent clusters. The univariate and multivariate linear regression was carried out so that the risk factors ...

Estudos recentes apontam para elevação da incidência e da gravidade das infecções por Staphylococcus aureus. Esse fato é agravado pela ampla disseminação de isolados de Staphylococcus aureus resistentes à meticilina (MRSA) nos hospitais, além de sua recente introdução na comunidade. A colonização nasal de indivíduos assintomáticos é o principal fator responsável pela persistência e disseminação de S. aureus nas populações humanas. Assim sendo, inquéritos de carreamento nasal são importantes para estimar a “carga” (burden) de S. aureus como um todo e de MRSA na comunidade. Além disso, a compreensão da relação bactéria-hospedeiro e dos fatores de virulência envolvidos se faz necessária para o combate às infecções que colocam em risco a vida da população em geral. O presente trabalho teve como objetivo investigar a distribuição de clones de Staphylococcus aureus e MRSA na população da área urbana de Botucatu, SP, identificando a prevalência dos determinantes de virulência junto aos fatores de risco associados em isolados obtidos da nasofaringe de indivíduos hígidos do município. Um total de 223 amostras de S. aureus isoladas de secreções nasais foi submetido a testes de susceptibilidade antimicrobiana à oxacilina e cefoxitina através da técnica de discodifusão. O método de E-test foi empregado para determinar a Concentração Inibitória Miníma (CIM) em amostras resistentes. Em seguida, foram realizadas reações de PCR para a detecção dos genes mecA, genes codificadores de fatores de virulência das enterotoxinas (sea, seb e sec) e toxina associada à síndrome do choque tóxico (tst); toxinas esfoliativas A e B (eta, etb), leucocidina de Panton-Valentine (lukS-PV e lukF-PV), hemolisinas alfa e delta (hla e hld); e biofilme (icaA e icaD). A tipagem molecular para a determinação dos clusters foi realizada pela técnica de PFGE. Para avaliar os fatores ...
Keywords: Staphylococcus aureus; Mucosa nasal - Infecções; Epidemiologia molecular; Fatores de risco; Virulencia (Microbiologia); Nasal mucosa